COMPORTAMENTO DO GLADÃOLO (Gladiolus grandiflorus (L.) ANDR. CV. SNOW PRINCESS CULTIVADO EM CINCO TIPOS DE SOLOS - Mattos, J. R.; Braga Jr, R. L. C.; Campos, H.; Moreira, C. S. (REVISTA DE AGRICULTURA, 2015)
COMPORTAMENTO DO GLADÃOLO (Gladiolus grandiflorus (L.) ANDR. CV. SNOW PRINCESS CULTIVADO EM CINCO TIPOS DE SOLOS